2022
DOI: 10.1101/2022.05.07.491032
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring the utility of recombinantly expressed snake venom serine protease toxins as immunogens for generating experimental snakebite antivenoms

Abstract: Snakebite is a neglected tropical disease that causes high rates of global mortality and morbidity. Although snakebite can cause a variety of pathologies in victims, haemotoxic effects are particularly common and are typically characterised by haemorrhage and/or venom-induced consumption coagulopathy. Despite polyclonal antibody-based antivenoms being the mainstay life-saving therapy for snakebite, they are associated with limited cross-snake species efficacy, as there is often extensive toxin variation betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 59 publications
1
1
0
Order By: Relevance
“…To assess whether the binding exhibited by the highest affinity ssDNA aptamers were capable of inhibiting the functional activities known from SVSPs, we first used degradation SDS-PAGE to explore protection against fibrinogenolysis. Our findings revealed that, in line with the known functional activities of native ancrod and batroxobin and recent work (76) both recombinantly expressed toxins cleaved the α-chain of fibrinogen (Figure 4A and 4B). We then assessed the inhibitory capability of the two candidate ssDNA aptamers at preventing this functional activity.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…To assess whether the binding exhibited by the highest affinity ssDNA aptamers were capable of inhibiting the functional activities known from SVSPs, we first used degradation SDS-PAGE to explore protection against fibrinogenolysis. Our findings revealed that, in line with the known functional activities of native ancrod and batroxobin and recent work (76) both recombinantly expressed toxins cleaved the α-chain of fibrinogen (Figure 4A and 4B). We then assessed the inhibitory capability of the two candidate ssDNA aptamers at preventing this functional activity.…”
Section: Resultssupporting
confidence: 91%
“…The recombinant toxins used in this study, Ancrod from C. rhodostoma and Batroxobin from B. atrox , were previously expressed in HEK293 mammalian cell lines (76). In this study, we used these toxins to conjugate to NHS-activated Sepharose® 4 Fast Flow beads (Sigma-Aldrich, UK) to generate ssDNA aptamers as novel toxin inhibiting therapeutics.…”
Section: Methodsmentioning
confidence: 99%